GERMAN EPITAPHS OF KLAIPĖDA REGION CEMETERIES IN THE 18–19TH CENTURIES IN THE CONTEXT OF PRUSSIAN EPITAPHS - BUKANTYTĖ, EGLĖ (Knygotyra, 2015)
The article reviews German tombstone inscriptions of Klaipėda Region Lutheran Cemeteries of the 18th and 19th centuries. German epitaphs are compared to inscriptions of neighbouring Prussian regions (some areas in North Poland and North Germany) regarding common traditions. The analysis also deals with the culture of writing and the traditions of the funeral oration with the aim of disclosing their parallels with tombstones inscriptions. Reasons for the choice of the language are discussed. Epitaphs are analyzed on the basis of the historical-comparative method. The small area and social similarity determine resemblances of style. The bilingualism of epitaphs in Klaipėda Region reflects the dominance of German language, using of cliches and being bilingualism as a natural part of everyday life.